INSTITUTIONAL EVALUATION: TOOL FOR PLAN OF IMPROVEMENTS OF HIGHER EDUCATION INSTITUTIONS (CIPEEX, 2022)
EVALUATION HAS BECOME A CORE ELEMENT OF CONTEMPORARY PEDAGOGICAL DISCOURSE. THIS IS NECESSARY TO HAVE A DIAGNOSIS OF THE TEACHING-LEARNING PROCESS (EVALUATION OF LEARNING) AND THE INSTITUTION (INSTITUTIONAL EVALUATION). BOTH CONTRIBUTE TO THE QUALITY OF EDUCATION AT ALL LEVELS. IT IS FROM THE PERSPECTIVE OF THE EVALUATION IN HIGHER EDUCATION THAT THIS STUDY IS INSERTED WITH THE PURPOSE OF ANSWERING THE QUESTION: WHAT IS THE IMPORTANCE OF THE INSTITUTIONAL EVALUATION TO LEAD THE IMPROVEMENT PLAN OF THE INSTITUTIONS OF HIGHER EDUCATION? THE OBJECTIVE IS TO ANALYZE THE IMPORTANCE OF THE EVALUATION TO GUIDE THE INSTITUTIONAL PLANNING. THE BIBLIOGRAPHICAL RESEARCH WITH A QUALITATIVE APPROACH WAS ADOPTED AS METHODOLOGY. FOR DATA ANALYSIS, THE CONTENT ANALYSIS METHOD WAS APPLIED, WHICH ALLOWS TO CLASSIFY AND CATEGORIZE ANY TYPE OF CONTENT. THE RESULTS POINTED OUT TWO CATEGORIES: THE FIRST THEORETICAL CONCEPTIONS OF EVALUATION; THE SECOND, INSTITUTIONAL EVALUATION IN HIGHER EDUCATION - TO KNOW TO INTERVENE. THE RESULTS EVIDENCED THE IMPORTANCE OF SELF-KNOWLEDGE IN ORDER TO RAISE AWARENESS OF THE STRENGTHS AND WEAKNESSES OF HIGHER EDUCATION INSTITUTIONS. FOR THIS, IT IS NECESSARY TO SEARCH FOR KNOWLEDGE OF WHAT IS IDEAL AND NECESSARY FOR THE QUALITATIVE FUNCTIONING OF INSTITUTIONS. ON THE OTHER HAND, THERE IS A NEED FOR ALL ACTORS TO BE INVOLVED IN THIS CONTINUOUS PROCESS OF SELF-KNOWLEDGE TO PROMOTE IMPROVEMENTS. IMPROVEMENTS THAT BRING SIGNIFICANT CHANGES TO THE STRATEGIES OF TEACHING, LEARNING AND ALL THE FUNCTIONING OF HIGHER EDUCATION INSTITUTIONS.
Keywords: Evaluation. Institutional evaluation.Higher education.Plan for improvement.